{Polygenic burden of short tandem repeat expansions promote risk for Alzheimer's disease - Guo, M. H.; Lee, W. P.; Vardarajan, B.; Schellenberg, G. D.; Phillips-Cremins, J. (medRxiv, 2023)
30 STR expansions had 3.62-fold higher odds of having AD and had more severe AD neuropathology. AD STR expansions were highly enriched within active promoters in post-mortem hippocampal brain tissues and particularly within SINE-VNTR-Alu (SVA) retrotransposons. Together, these results demonstrate that expanded STRs within active promoter regions of the genome promote risk of AD.